2014
DOI: 10.1371/journal.pone.0104533
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cysteine-Sparing NOTCH3 Mutation in a Chinese Family with CADASIL

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is an adult onset cerebral small vessel disorder caused by the mutations of the neurogenic locus notch homolog protein 3 (NOTCH3) gene. The extracellular part of NOTCH3 is composed of 34 epidermal growth factor-like (EGF-like) repeat domains. Each EGF-like domain is rich of cysteine and glycine to produce three loops that are essential for high-affinity binding to its ligand. Nearly all reported CADASIL-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…All the mutations, with the exception of p.R75Q, p.R75P and p.T1098S, lead to an odd number of conserved cysteine residues in the EGF-like domain. It has already been reported that NOTCH3 gene mutations not involving cysteine residues in a few cases, showing a later disease onset and a lower and milder clinical course than typical CADASIL patients with mutations involving cysteine residues [11,20]. However, those three patients with cysteine-sparing mutations exhibited similar clinical manifestations as other typical patients in our study.…”
Section: Genotype Spectrum and Biopsy Results Of The Patients Diagnosesupporting
confidence: 67%
See 3 more Smart Citations
“…All the mutations, with the exception of p.R75Q, p.R75P and p.T1098S, lead to an odd number of conserved cysteine residues in the EGF-like domain. It has already been reported that NOTCH3 gene mutations not involving cysteine residues in a few cases, showing a later disease onset and a lower and milder clinical course than typical CADASIL patients with mutations involving cysteine residues [11,20]. However, those three patients with cysteine-sparing mutations exhibited similar clinical manifestations as other typical patients in our study.…”
Section: Genotype Spectrum and Biopsy Results Of The Patients Diagnosesupporting
confidence: 67%
“…Eight studies described mainland Chinese patients with CADASIL caused by NOTCH3 gene mutation [4,7,9,[11][12][13][14][15][16]. We performed clinical and genetic reanalysis of CADASIL patients in mainland China using the data from our study and those in other studies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Although whether patients with several cysteine-sparing NOTCH3 mutations develop CADASIL remains to be clarified [1,10,13,[25][26][27][28][29], we clearly showed patients with this Arg75Pro mutation had deposits of the extracellular domain of Notch3 on vascular walls, which indicates that those patients are developing CADASIL. The Arg75Pro mutation was reported in Korean and Japanese CADASIL patients but was not found in Chinese and Caucasian patients [13,23].…”
Section: Discussionmentioning
confidence: 98%